Fabrication of high-aspect-ratio aluminum oxyhydroxide nanopillars for anti-reflection surfaces. (27th October 2017) - Don Han, Eui; Kim, Byeong Hee; Seo, Young Ho
Abstract: This study presents the anti-reflection characteristics of high-aspect-ratio aluminum oxyhydroxide nanopillars prepared by the hydrothermal synthesis method from a nanoporous alumina substrate. Three different alumina-based nanostructures, including nanolens, short-nanopillar, and long-nanopillar were prepared, and the center-to-center distance of the nanostructures was fixed as 380 ± 50 nm. The diameter of the nanopillars was 140 ± 30 nm, and the aspect ratios of the short and long nanopillars were 1.5 and 4.0, respectively. From visual investigation, the surfaces of fabricated aluminum oxyhydroxide nanopillars appear black, although they did not have any black color. The anti-reflection characteristics of high aspect ratio aluminum oxyhydroxide nanopillars were compared with those of an alumina nanolens array. According to the experimental results, the high-aspect-ratio aluminum oxyhydroxide nanopillar array demonstrated remarkable anti-reflection characteristics, with 0.18% reflectance at an incident angle of 15°.